ESTIMATES OF TECHNO-ECONOMIC LOSS FROM CONVERTING SAWNWOOD TO FURNITURE PARTS IN A DESIGNATED WOOD PROCESSING OUTFIT - Larinde, Solomon Lagbenga; Erakhrumen, Andrew Agbontalor (Floresta, 2020)
Q Quantification and reduction of residues generated through wood conversion are important in wood resources management. This study was carried out, to contribute to this, by using air-dried sawnwood from three tropical hardwood (Afzelia africana, Milicia excelsa and Tectona grandis) with mean dimension 117x305x1830mm to produce furniture parts of dimensions 25(+3)mm x 600(+20) mm/900(+20) mm/120(+20) mm/150(+20) mm/180(+20) mm/2100(+20)mm with the generated wood residues categorised and quantified. Data were analysed using descriptive statistics, analysis of variance, least significant difference for separating means and regression analysis having technical and economical residues as dependent variables for the three species. Mean total input volume ranged from 23.11±2.98m3 to 24.63±0.55m3 for A. africana and T. grandis respectively while that for gross and net output volume ranged from 12.01±1.78m3 to 16.44±0.38m3 and 9.52±1.42m3 to 14.44±0.38m3 for A. africana and T. grandis respectively. Economical residues ranged from 2.00±0.10m3 to 2.49±0.40m3 and economical residues as percentage of gross output volume ranged from 12.23±0.64m3 to 20.73±2.59m3 for T. grandis and A. africana respectively while the range was from 10.19±0.25m3 to 13.59±1.83m3 for T. grandis and A. africana respectively for total volume of residues. Additionally, mean percentage gross and net recovered volume ranged from 50.27±2.42% to 67.22±0.34% and 41.21±2.32% to 58.58±0.62% for A. africana and T. grandis respectively. Total percentage volume of residues was least for T. grandis (41.42±0.62%) and highest for A. africana (58.79±2.32%). Based on these outcomes, it was recommended that increased effort is needed to improve capacities and facilities for lesser generation of residues during mechanical wood processing.